0268 Characterization of Neurodegenerative Disorder Subtypes Based on Non-REM Hypertonia and Sleep Spindle Duration. (25th May 2022) - Levendowski, Daniel; Boeve, Bradley; Walsh, Christine; Tsuang, Debby; Salat, David; Hamilton, Joanne; Lee-Iannotti, Joyce; Shprecher, David; Berka, Chris; Westbrook, Philip; Mazeika, Gandis; Neylan, Thomas; et al.
Abstract: Introduction: Increased non-REM hypertonia (NRH) and decreased sleep spindle-durations were found to be independently associated with patients broadly characterized as presumed Parkinsonian-spectrum disorder [i.e., dementia with Lewy Bodies/Parkinson Disease Dementia (DLB/PDD), Parkinson Disease (PD), progressive supranuclear palsy (PSP), or isolated REM sleep behavior disorder (iRBD)] when compared to subjects with Alzheimer Disease dementia (AD), mild cognitive impairment (MCI) and normal cognition (NC). In this investigation, the NRH and spindle-duration features were combined to determine whether these biomarkers could distinguish neurodegenerative disorder subtypes. Methods: This multicenter investigation included analysis of several neurodegenerative disorder patient subtypes including: DLB/PDD (n=16), PD (n=16), iRBD (n=19), PSP (n=13), AD (n=22), MCI (n=35), and NC (n=61). Sleep Profiler (SP) studies were conducted in all participants. NRH was auto-detected based on persistently elevated electromyographic (EMG) power relative to delta, theta, and sigma bands, while spindles were recognized by temporal excursions in alpha and sigma power > 250-milliseconds. With NRH >5% of sleep-time and spindle-duration <1-minute considered abnormal, tallies were compared across neurodegenerative disorder subtypes with Fisher Exact tests. Results: Combined SP features of Normal-NRH/normal-SpD were greater in the NC (56%), AD (46%), and MCI (43%) subtypes versus PSP (8%) and DLB/PDD (6%), and when iRBD (21%) was compared to NC (all P<0.05). Abnormal-NRH/abnormal-SpD were more frequent in PSP (85%) and DLB/PDD (75%) subtypes versus iRBD (26%), PD (25%), MCI (11%), AD (9%), and NC (8%)(all P<0.02). Abnormal-NRH/normal-SpD were greater in iRBD (47%) compared to MCI (14%), NC (8%), PSP (8%), DLB/PDD (6%), and AD (5%) subtypes, and in PD (31%) versus NC (all P<0.05). Normal-NRH/abnormal-SpD occurred more often in AD (41%) than iRBD (5%) and PSP (0%)(both P<0.05). Conclusion: The combination of NRH and spindle-duration abnormality occurred more frequently in DLB/PDD and PSP subtypes. Abnormal NRH with normal sleep-duration was more frequent in iRBD and PD subtypes. Normal NRH and spindle-duration occurred most often in NC and MCI types. AD exhibited normal NRH with isolated cases of either normal or abnormal spindle-duration. Our preliminary findings suggest that auto-detected sleep biomarkers may aid in the characterization of neurodegenerative disorder subtypes. Larger prospective cohort studies are needed. Support (If Any): NIA grants: R44AG050326, R44AG054256, P30AG62677 and R34AG56639.